The Perception of Non-Moslem Customers Towards Bank Syariah in Manado City - Laily Nurhayati; Silvya L. Mandey; Rita N. Taroreh; Irvan Trang; Radjab Djamali (AIBPM Publisher, 2021)
The development of syariah banks in Manado city as the capital of North Sulawesi province which has a large number of non-moslem population is quite fast. The bank has many non-moslem customers, even one of the subsidiaries has more non-moslem customers than Moslem customers. This present study aims to describe the perception of non-moslem customers towards bank syariah in Manado city. This research uses a case study approach which is part of qualitative research. Data collection was carried out by participant observation, interviews and documentation. After the analysis was conducted, the result of the study revealed the perception of non-moslem customers toward bank syariah in Manado city was dominated consecutively by the affective (emotional), cognitive (perceptual) and conative (action) components.